An Assessment of Pawpaw Leaf Meal as Protein Ingredient for Finishing Broiler - Onyimonyi, A.E.; Ernest, Onu (International Journal of Poultry Science, 2009)
A feeding trial was conducted to evaluate the effect of dietary inclusion of Pawpaw Leaf Meal (PLM) on the performance of finishing broilers. Sixty 5 weeks old broilers were used for the study that lasted for 28 days. The sixty birds were assigned to four dietary treatments with fifteen birds per treatment in a Completely Randomized Design. Each treatment was replicated thrice. Four isonitrogenous and isocaloric broiler finisher diets containing 21% CP and 2800kcalME/kg were formulated. PLM was incorporated at levels of 0.5, 1.5 and 2.0% in treatments 2, 3 and 4 respectively. Treatment 1 had no PLM and was used as the control diet. Results should that the effect of treatments on final body weight, weight gain, daily weight gain, feed conversion ratio and feed cost/kg gain were significant (P